Penerapan Metode COPRAS Untuk Seleksi Pemuda Pelopor Tingkat Nasional dan Provinsi Sumatera Utara - Ester Rajagukguk (ADA Journal of Information System Research, 2024)
The pioneer youth programme is the flagship government programme of the North Sumatra Youth and Sports Service. This program was developed with the aim of encouraging a pioneering spirit among youth, finding youth who have pioneering potential in developing their potential to create something real that is of quality and carried out consistently and persistently which benefits the community and is recognised by various parties and the government. However, there are often mistakes in the selection of pioneer youth. The problem faced by the selection team is how to determine outstanding youth from a number of alternative youth who have the ability to pioneer so that it is less targeted in providing the best value to be analysed. To anticipate that there will be no errors in the selection of Pioneer Youth, a Decision Support System is needed. One method that can be used for Decision Support Systems is to use COPRAS (Complex Proportional Assessment). The research was conducted by finding the weight value for each attribute, then a ranking process was carried out which would determine the optimal alternative. It is hoped that the results of this research can help the Selection Team in determining youth who deserve to be pioneer youth. The final results showed that Dedy was recommended as a pioneer youth at the national and provincial levels in North Sumatra with a final score of 100.